Kulturella perspektiv på skam: En inledning - Marander-Eklund, Lena; Metsämäki, Lina (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2020)
Shame is an emotion that we encounter in many everyday situations in the western world. In this introduction, we, the editors of this issue, intend to provide some guidance to a field that is complex and rich with many different perspectives. Shame can be seen as an affect, emotion or feeling depending on the perspective. Characteristic of shame as an emotion is that it is a social and culturally specific emotion in the way that it is experienced as a negative self-assessment that is based on how a person think she is being viewed by real or imaginary others. It is linked to power and cultural norms. In this number two central themes linked to shame emerged; gender and environmental issues. This is not because these are the only areas where studies of shame from a cultural perspective may be productive but can be seen as an indication that cultural processes and changing norms in society may benefit from an analysis of shame.